Pengaruh Harga, Promosi, Lokasi, Kelengkapan Produk dan Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Empiris Pada Konsumen Indomaret di Kabupaten Karanganyar) - Nur Prabowo, Wahyu; , Drs. Wiyadi, M.M., Ph.D (2015)
It is inevitable that recently there has been a growing number of minimarkets or shopping centers being introduced; offering daily needs. Nowadays, talking about shopping center does not merely deal only with its size, but also with its facility, parking space availability, waiting room's state of comfort, traffic condition, access and, the important one, its price range. Recent growing number of introduction of shopping centers enables customers to have options in buying products. This research aims to analyze the influence of price, promotion, location, product assortment, service quality, on customer's satisfaction perceived by customer of Indomaret in Karanganyar. By approaching as descriptive research, this research attempts to describe correlated objects used as consideration to make general decisions. The population of this study is anyone who have purchased products in any Indomaret in Karanganyar, with 100 respondents being taken as the sample of this study. Whilst the sampling method used is purposive sampling, the data collecting relies on questionnaires. The multiple regression results as follow, Y = 8,439 + 0,176X1 + 0,101X2 + 0,062X3 + 0,148X4 + 0,051X5. Independent variables with most influence on customer satisfaction are as follows: price (0,176), promotion (0,101), location (0,06), product assortment (0,148), and service quality (0,051). T test proves that all independent variables (price, promotion, location, product assortment, service quality) positively influence customers' loyalty of Indomaret in Karanganyar. With the determination number reaching 40.9 %, it can be argued that price, promotion, location, product assortment, service quality make up 40,9 % customers' loyalty, while the rest, 59,1 %, is influenced by other variables not involved in this study.